Partisan Bias in Fund Portfolios - Wintoki, M. Babajide; Xi, Yaoyi (Journal of Financial and Quantitative Analysis, 2020)
We document that fund managers are more likely to allocate assets to firms managed by executives and directors with whom they share a similar political partisan affiliation. We find that this bias is not associated with improved fund performance. Funds with more partisan bias suffer from higher levels of idiosyncratic volatility than those with less bias. Partisan bias is more evident when fund managers are less experienced, in more informationally opaque firms, and when the U.S. president comes from fund managers’ own party. These findings suggest that political partisan bias among fund managers may be due to in-group favoritism.